Uncertainty work as ontological negotiation: adjudicating access to therapy in clinical psychology - Pickersgill, Martyn (Sociol Health Illn, 2019)
Across the UK, wide‐ranging efforts have been made to enhance citizen access to psychological therapy. Clinical psychologists are key providers of and gatekeepers for therapy. This article is concerned with how clinical psychologists foster access (or not) to psychological care. More specifically, it interrogates how psychologists manage, and make decisions around, patient referrals. Following a referral, psychologists must resolve an uncertain situation: should they accept a referral and continue with an assessment? Thereafter, they must decide whether a patient is suitable for their service – and for therapy more generally. Certainty is synthesised against a backdrop of sometimes powerful pressures to meet service targets. Taking cues from medical sociology and science and technology studies (STS), this article interrogates some of the uncertainties around access to psychological therapy, and how decisions made by clinical psychologists involve negotiations of patient, service and professional ontologies. To do so, it draws on interviews with 40 psychologists across England and Scotland. The paper spotlights a professional group that is often absent from or only dimly lit within sociological observation and analysis: clinical psychology. Through attending to the discourses of psychologists, I extend conversations about uncertainty through a distinctive case study.